Bronchiectasis and asthma: a dangerous liaison?. Issue 1 (February 2019) - Crimi, Claudia; Ferri, Sebastian; Crimi, Nunzio
Abstract : Purpose of review: To explore the latest insight of the literature on the asthma/bronchiectasis phenotype providing an updated overview about epidemiological, clinical and biological evidence linking these two conditions. Recent findings: An increasing body of literature has shown that the association of asthma and bronchiectasis is a frequent phenomenon leading to a more severe disease with frequent exacerbations. The mechanisms by which the two diseases are linked are still not well established but they share several clinical and immunological features and many comorbidities. Summary: The early identification of bronchiectasis through high-definition computer tomography in patients with severe asthma is crucial in order to provide an adequate treatment for both diseases and therefore to better control symptoms, exacerbations and infections.